Economic complexity and structural transformation: the case of Mozambique - Bjørn Bo Sørensen; Christian Estmann; Enilde Francisco Sarmento; John Rand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Mozambique is among the world's least complex economies. By systematically accounting for both supply- and demand-side factors, we identify new products and sectors that can help to diversify and upgrade its economy. In a supply-side analysis, we use network methods from the literature on economic complexity to identify a set of target products that are complex, require productive capabilities useful in the export of other products, and are close to Mozambique's existing productive structure. In a demand-side analysis, we use gravity models to predict the export potential of target products and markets given product-specific trade resistance and geographically dispersed demand. The broad sectoral focus of Mozambique's industrial policy is largely consistent with structural transformation and export promotion. The current prioritization of agriculture, agro-industry, and metals is especially important, while there are unexploited opportunities in machinery, vehicles, and transport equipment. We find some potential for Mozambique to export target products to neighbouring countries.
Keywords: C53; F14; O14; O25; 330; economic complexity; trade; export upgrading; structural transformation; Mozambique